Dampak Suasana Toko, Persepsi Harga, dan Kualitas Produk Terhadap Keputusan Pembelian: Studi Kasus di Kedai Roti Ibu Saya, Depok - Rahmawati, Putri; Cyasmoro, Verry (Indonesian Journal Publisher, 2024)
This study aims to analyze the influence of store atmosphere, price perception, and product quality on purchasing decisions at Kedai Roti Ibu Saya, Depok. The research employs a quantitative descriptive methodology using an accidental sampling technique. A total of 100 respondents were selected as the study sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 25 software. The results reveal that, partially, the store atmosphere (H1) does not significantly affect purchasing decisions, whereas price perception (H2) and product quality (H3) have a significant influence. Simultaneously, store atmosphere, price perception, and product quality collectively impact purchasing decisions. The findings emphasize the importance of enhancing competitive price perceptions and product quality to optimize customers' purchasing decisions. It is recommended that the management of Kedai Roti Ibu Saya improve facilities and services, such as providing a more comfortable space layout, employee training, and operational efficiency improvements. Regular maintenance of customer facilities is also advised. These efforts are expected to strengthen customer appeal and satisfaction while sustainably increasing purchasing decisions.